2004
DOI: 10.3141/1867-19
|View full text |Cite
|
Sign up to set email alerts
|

Inclement Weather and Traffic Flow at Signalized Intersections: Case Study from Northern New England

Abstract: Gridlock along arterial systems in New England is often the result of adverse weather conditions, which can render the normal signal plans unsuitable. The current study has two main objectives: ( a) to assess the impact of inclement weather on traffic flow parameters at signalized intersections in northern New England and ( b) to evaluate the likely operational benefits of implementing special timing plans for inclement weather conditions. A signalized intersection in Burlington, Vermont, was selected, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…TRANSYT calculates the optimal signal timings for a given road network model by minimising a performance function consisting of delay, number of stops, and economic factors. TRANSYT has been shown to reduce delay up to 24% over pre-existing signal timing plans in the New England region of the USA [8].…”
Section: A Related Workmentioning
confidence: 99%
“…TRANSYT calculates the optimal signal timings for a given road network model by minimising a performance function consisting of delay, number of stops, and economic factors. TRANSYT has been shown to reduce delay up to 24% over pre-existing signal timing plans in the New England region of the USA [8].…”
Section: A Related Workmentioning
confidence: 99%
“…Lu and Pernıá (2000) analyzed the effect of the proportion of elderly people on l1 and on saturation headways. Agbolosu-Amison (2004) analyzed the effect of climate on l1 and on saturation headways. Khosla and Williams (2006) evaluated the effect of green time on queue discharge.…”
Section: The Effect Of Motorcycles On Signalized Intersection Operationsmentioning
confidence: 99%
“…The decrease in free flow speed ranged from 10 to 30%, depending on type of the analysed weather conditions (from rain to slushy paths and wheel road surfaces condition) while the decrease of the saturation flow rate ranged from 6 to 20% (from rainy to snowy and sticking road surfaces condition). A research on the adverse weather impact at a signalised intersection in Burlington (Vermont) was aimed at examining the adverse weather impact on traffic flow characteristics, taking into consideration the longitudinal inclination on one of the intersection legs (Agbolosu-Amison et al 2004). The results showed that under the precipitations there was a lower impact on the saturation flow rate reduction at the intersection leg with inclination (4%), in comparison with intersection leg without inclination (7%).…”
Section: Literature Reviewmentioning
confidence: 99%